The Use of Quasi Monte Carlo Method with Halton Random Number Sequence in Determining the Price of European Type Options: in PT Telekomunikasi Indonesia Stock’s - Putri, Sherina Anugerah; Subartini, Betty; Sukono, Sukono (iora, 2022)
An investor must be wise in managing the funds he has to carry out investment activities. Investors can use options as an alternative to investing because they can increase profits and avoid investment risks. Options are one of the most widely used derivative products. The main problem when entering into an option contract is determining the right price to be paid by the option buyer to the option seller. This research was made to determine the price of European-type stock options. Case studies on PT Telekomunikasi Indonesia, Tbk shares in the 2021-2022 period. The analysis was performed using the Quasi-Monte Carlo method with Halton's random number sequence. Based on the results of this study, it is expected to be a consideration in deciding to buy European-type stock options at PT Telekomunikasi Indonesia, Tbk